Survival benefit of perioperative chemoradiotherapy in patients with resectable primary gastric adenosquamous carcinoma: a population-based cohort study - Wu, Di; Li, Jie; Dai, Bai-Shu; Song, Qi-Ying; Chen, Peng; Gu, Ming-Yu; Zhao, Bing-He; Liu, Lu; Chang, Zheng-Yao; Gao, Wen-Xing; Zhao, Wen; Li, Shuo; et al. (Frontiers in Oncology, 2025)
BackgroundCurrently, whether Gastric adenosquamous carcinoma (GASC) can benefit from perioperative chemoradiotherapy (pCRT) remains controversial. The objective of this study was to evaluate the survival benefit of pCRT in resectable GASC.MethodsPatients diagnosed with GASC were selected from the Surveillance, Epidemiology, and End Results (SEER) Program and our medical center. Enrolled patients were stratified into two cohorts according to whether they underwent perioperative chemotherapy and radiotherapy or not, and the overall survival (OS) and cancer-specific survival (CSS) of the two cohorts were compared. Subsequent subgroup analysis was performed to identify the population that could demonstrably benefit from chemoradiotherapy.ResultsWe screened almost 180,000 cases of gastric malignant neoplasms. Finally, only 267 patients with GASC met the inclusion criteria and were eventually included in the study, with 147 and 120 patients in the pCRT and non-pCRT groups, respectively. The baseline information of the two groups showed no statistically significant differences. Patients in the pCRT group had superior OS (26.0 vs. 13.0 months, p=0.002) and CSS (26.0 vs. 14.0 months, p=0.004). Univariate and multivariate COX regression analyses demonstrated that pCRT was an independent protective factor for favorable OS and CSS with in patients with GASC and age, race, tumor size, T stage, N stage and TNM stage were also independent predictors of survival. Subgroup analysis indicated that the GASC population aged ≤ 66 years, non-EGJ, tumor > 5 cm, tumor differentiation degree 3-4, T3-4 stage, N2-3, and TNM III-IV could significantly benefit from pCRT. The combined chemotherapy with radiotherapy group significantly improved OS and CSS of GASC compared to chemotherapy alone.ConclusionsThis retrospective study verified that pCRT could improve the long-term OS and CSS of patients with GASC. Subgroup analysis found that patients with aged ≤ 66 years, tumor differentiation grade 3-4, T3-4, N2-3, and TNM III-IV could gain significant benefits from perioperative chemoradiotherapy. Moreover, the study demonstrated that patients with GASC receiving combined radiotherapy and chemotherapy had superior OS and CSS compared to those receiving chemotherapy alone, implying the crucial role of radiotherapy. This study provides an excellent evidence-based medical reference for GASC treatment.